Search Engine Advertising: Channel Substitution When Pricing Ads to Context - Goldfarb, Avi; Tucker, Catherine (Management Science, 2011)
We explore substitution patterns across advertising platforms. Using data on the advertising prices paid by lawyers for 139 Google search terms in 195 locations, we exploit a natural experiment in “ambulance-chaser” regulations across states. When lawyers cannot contact clients by mail, advertising prices per click for search engine advertisements are 5%–7% higher. Therefore, online advertising substitutes for offline advertising. This substitution toward online advertising is strongest in markets with fewer customers, suggesting that the relationship between the online and offline media is mediated by the marketers' need to target their communications. This paper was accepted by Pradeep Chintagunta, marketing.